Codesigning culturally safe oral health care with First Nations Kidney Warriors experiencing kidney disease in South Australia - Janet Kelly; Kelli Owen; Kate Tyrell; Kelly Clemente; Margie Steffens; Nari Sinclair; Sylvia Reynolds; Wade Allan; AKction - Aboriginal Kidney Care Together - Improving Outcomes Now project (BMC, 2024)
Abstract Background This paper describes how First Nations Kidney Warriors (Aboriginal and Torres Strait Islander people living with kidney disease), dental hygienists, kidney health care professionals, an Aboriginal hostel accommodation manager and researchers co-designed an approach to improve oral health in South Australia. Kidney Warriors have strong connection to Country, Community and family that underpins health, wellbeing and approaches to research. However, significant colonisation, racism and marginalisation have impacted Kidney Warriors' social, cultural and financial determinants of health, leading to increased chronic conditions including kidney disease. Access to culturally safe, affordable and responsive oral health care is vital but challenging for First Nations Peoples undergoing dialysis and kidney transplantation; Australian oral health care is generally provided privately, in metropolitan centres, by professionals who may hold unconscious bias about First Nations Peoples and incorrect assumptions regarding equal access to care. Methods The AKction - Aboriginal Kidney Care Together Improving Outcomes Now kidney care oral health working group codesigned strategies to address disparities and gaps in care, and co-create more accessible, responsive, culturally safe and sustainable models of care. A decolonising and collaborative participatory action research was informed by Dadirri Deep Listening and Ganma Knowledge Sharing with repeated cycles of Look and Listen, Think and Discuss, Take Action Together. A small pilot evaluation survey of clinical placement in an Aboriginal setting was undertaken. Results Four phases of collaboration were undertaken. Community and health professional consultations identified key gaps and priorities. Clinical yarning and cultural safety training and an interprofessional skills day was co-facilitated. Dental hygienist student clinical placement at Kanggawodli Aboriginal Hostel was initiated and evaluated. First Nations Kidney Warriors were positioned as educators and experts of their own lives and health care needs. A new framework for kidney health-oral health cultural safety and clinical education was developed. Conclusion This codesigned approach involving inter-professional collaboration and joint decision making with community members has significantly informed improvements in oral health care information, services and referral with and for First Nations Peoples with kidney disease. This project provides a working example of how to decolonise health service and education programs from the ground up. Trial registration NHMRC PAR 2004389.